2020
DOI: 10.1177/0040517520925559
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between drying parameters and drying performance in domestic tumble dryers

Abstract: The purpose of this study is to investigate the effect of drying parameters on drying performance in an air-vented tumble dryer, and to optimize its drying performance by adjusting parameters. The critical drying parameters that influenced specific moisture extraction rate (SMER), final moisture content, evenness of drying, and smoothness appearance were determined by the analysis of variance in JMP software, which were rotational speed of the motor and load size, with clearly significant individual effects an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Drum scaling effects have not yet been systematically measured and analyzed in open literature; however, they were approached indirectly through dimensional analysis. Studies [7,29] have shown that drum dimensions (radius, volume) are relevant in many non-dimensional groups that can be used to model the tumble dryer energy efficiency. Furthermore, drum radius together with drum speed defines the centrifugal force acting on fabrics, which is one of key factors that affects the fabric motion patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drum scaling effects have not yet been systematically measured and analyzed in open literature; however, they were approached indirectly through dimensional analysis. Studies [7,29] have shown that drum dimensions (radius, volume) are relevant in many non-dimensional groups that can be used to model the tumble dryer energy efficiency. Furthermore, drum radius together with drum speed defines the centrifugal force acting on fabrics, which is one of key factors that affects the fabric motion patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Though not aimed at detailed analysis of parameters affecting the evenness of drying, the study demonstrated that the RMC i distribution for a 3.83 kg load depended on the types of cloths in the load. A more detailed study of evenness of drying was conducted by Yu et al [29] in a commercial air vented tumble dryer with a rated capacity of 10 kg. The drying experiment was performed at different drum motor speeds (800, 1000 and 1200 rpm), air velocities (4.8, 7.8 and 10.8 m/s) and constant heater power 3000 W. Three cotton loads of 1, 3 and 5 kg according to the GB/T 8629 [30] were used.…”
Section: Introductionmentioning
confidence: 99%
“…At R 50/57.5(0) and R 50/ 57.5(1), the sample moved at a speed nearly equal to the drum rotational speed at the positions close to the drum wall due to the centrifugal force. However, in the case of R 50/57.5 (9) and R 50/57.5 (29), the sample did not continuously rotate along the drum wall and fell due to the change in the drum rotational direction, thereby passing through various positions.…”
Section: Effect Of Changing the Speed And Direction Of Drum Rotation ...mentioning
confidence: 98%
“…In the XY plane, the total drying loads filled the internal space of the dryer at R 50/57.5(0) and R 50/57.5 (1). For frequent changes in the direction as in the case of R 50/57.5 (9) and R 50/57.5 (29), the total drying loads were observed to be actively mixed, and they were agglomerated or spread due to several changes in the outlines. When the drum temporarily stopped for a change in direction, we observed that the sample and the dummy loads agglomerated as they fell toward the bottom of the drum, and then they were spread out again by the centrifugal force when the rotation of the drum resumed.…”
Section: Movement Patterns Representing the Outlines Of The Total Dry...mentioning
confidence: 98%
See 1 more Smart Citation